Conventional Neural Network Time Series Models on Roof Materials Costs Indices Data - Azura Md Ghani, Nor; Bin Ahmad Kamaruddin, Saadi; Musirin, Ismail; Hashim, Hishamuddin (International Journal of Engineering and Technology, 2019)
The Construction Financial Management Association (CFMA) found that two-thirds of participant contractors identify variability in construction as an important risk affecting profits. Varieties in construction costs also have negative and horrible effects on public or private proprietor associations.Gradual changes in Construction Costs Indices (CCI) affect the accuracy of engineering cost estimates for proprietors causing construction projects to be delivered with higher costs, schedule delays, and several insolvencies. Reliable forecasting for future construction costs would help to guarantee spending plans and limited resources allocations more appropriately. Estimating costs based on such indexes are adopted widely in the construction industry (by (1) associating the total cost of a facility with several major parameters of the facility, such as size, system, and location; and (2) analysing the trend of indexes relevant to construction costs over time.This research implements two models which are backpropagation neural nonlinear autoregressive (BPNN-NAR) and backpropagation neural nonlinear autoregressive moving average (BPNN-NARMA) on Malaysian Roof Materials dataset. The best model for this data is BPNN-NAR models with 10-10-10 configurations based on RMSE=0.414. It is expected that this research is significant towards helping the policy makers and contractors to make proper decisions, biddings and budgeting on the nationâ€™s infrastructure projects.Â